MENINGKATKAN PRESTASI BELAJAR SISWA DALAM PELAJARAN MATEMATIKA UKURAN PEMUSATAN DATA MELALUI MODEL PEMBELAJARAN MAKE A MATCH PADA SISWA KELAS XII AKL 1 SMK NEGERI I LIWA - KASIYATUN KASIYATUN (VOCATIONAL: Jurnal Inovasi Pendidikan Kejuruan, 2022)
Based on the results of the first daily test of class XII students, especially class XII AKL1 at SMK Negeri I Liwa in mathematics subjects related to basic competencies Data Concentration Measures, it can be seen that those who get the complete criteria score are 46.15%, while those who have not completed are 53, 85%. This shows that the results of children's achievement in mathematics are still low. This is indicated by the low class average of 58.08 with the highest student score of 100 and the lowest student score of 20. from several factors causing the low student learning outcomes. The use of teaching methods that are mostly carried out by teachers prioritize the role of the teacher, this happens because the teacher is oriented towards completing quite a lot of material, while the time available is quite limited, so the lecture learning method dominates in learning activities which causes the role of students to be reduced and in the end learning outcomes the achievement was less than the kkm, namely 65. Student learning outcomes increased, the atmosphere showed positive changes, namely a new conducive atmosphere in learning activities, teacher performance increased, especially in developing learning models. The increase in students' learning motivation can be seen from the results of the evaluation tests of students of class XII AKL1 in the third cycle of the second meeting with an average of 78.08, meaning that the mathematics value of class XII AKL1 for Competency Measures of Data Centering is above the KKM value. ABSTRAKBerdasarkan hasil ulangan harian pertama siswa kelas XII, khususnya kelas XII AKL1 di SMK Negeri I Liwa pada mata pelajaran matematika yang berkaitan dengan kopetensi dasar Ukuran Pemusatan Data terlihat bahwa yang mendapat nilai kriteria tuntas sebesar 46,15%.sedangkan yang belum tuntas sebesar 53,85%. Hal ini menunjukkan bahwa hasil prestasi anak pada pelajaran matematika masih rendah. Hal ini ditunjukkan dengan masih rendahya rata-rata kelas yakni 58,08 dengan nilai siswa tertinggi 100 dan nilai siswa terendah 20. dari beberapa faktor penyebab rendahnya hasil belajar siswa. Penggunaan metode mengajar yang sebagian besar dilakukan guru mengedepankan peran guru, hal ini terjadi karena guru berorentasi pada penyelesaian materi yang cukup banyak, sementara waktu yang tersedia cukup terbatas, sehingga metode pembelajaran ceramah mendominasi dalam kegiatan pembelajaran yang menyebabkan peran siswa berkurang dan pada akhirnya hasil belajar yang diraihpun kurang dari kkm yaitu 65. Hasil belajar siswa meningkat, Suasana menunjukkan perubahan positif yaitu suasana baru yang kondusif dalam kegiatan pembelajaran, Kinerja guru meningkat terutama dalam mengembangkan model pembelajaran. Peningkatan motivasi belajar siswa dapat di dilihat dari hasil tes evaluasi siswa kelas XII AKL1 pada siklus ke III Pertemuan ke-dua dengan rata-rata 78,08 artinya nilai matematika kelas XII AKL1 untuk Kompetensi Ukuran Pemusatan Data di atas nilai KKM.